Assessment of Summer Overheating in Concrete Block and Cross Laminated Timber Office Buildings in the Severe Cold and Cold Regions of China - Yu Dong; Rong Wang; Jing Xue; Jingran Shao; Haibo Guo (Buildings, 2021)
The aims of the paper were to clarify whether office buildings in the severe cold and cold regions are overheating, especially those with natural ventilation, and whether potential overheating is related to the building materials. The severe cold and cold regions of China were considered to be cool regions during summer. However, with global warming, improvements in the thermal performance of the building envelope and the urban heat island effect, office buildings in these regions are showing different degrees of overheating during summer. Two office building materials commonly used in this area, cross laminated timber (CLT) and concrete block, were simulated in this study. With reference to the overheating standard, the degree of overheating in six cities in the severe cold and cold regions was quantitatively analysed and the extent of overheating for the two building materials was compared. Finally, the influence of thermal insulation on building overheating is discussed, and some suggestions are put forward to improve the relevant national regulations in China. The results show that office buildings in the severe cold and cold regions experience overheating during summer, and CLT buildings are more prone to overheating than concrete buildings during summer. This is attributable to the different thermal mass of the materials. Thick insulation does increase the risk of building overheating, and the effect on concrete buildings is more pronounced. Concrete buildings with an insulation layer can experience overheating for 27–71 h more than buildings without an insulation layer. Insulation on CLT buildings only results in an increase of 11–37 h. When considering the current situation with summer overheating in the severe cold and cold regions, relevant codes should also be modified and improved accordingly to guide building design, so as to achieve low-carbon and energy-saving goals.